MANUFACTURING OF BIODEGRADABLE LUBRICANTS FROM GLYCEROL AND CITRIC ACID - KRISTIANTO - NIM: 23016012, YAKOBUS
Environmental pollution is now largely due to the use of products that damage the environment, destroy ozone, and also because the process of decomposition of products after use takes a long time. One of the efforts being made today is calling for the use of biodegradable products that decompose rapidly to the environment. This study aims to make environmentally friendly lubricants when conventional lubricants are in need of a long time to decompose by the environment. In general, this research is divided into 2 stages, namely polymerization stages and analysis of research results. The polymerization step is carried out by variation of the mole ratio between citric acid and glycerol, which then remnant excess glycerol is reacted with oleic acid according to stoichiometric ratio, and temperature variation. The variation of mole ratio of citric acid and glycerol to be used is 1: 3; 1: 4; 1: 5; and 1: 6. The temperature variations to be used are 90oC, 120oC, and 150oC. The polymerization process time is 4 hours. The oleic acid is added when the polymerization process has been running for 3 hours and the polymerization process is continued for 9 hours. The analysis to be performed is the analysis of acid numbers, density, and viscosity, and theoretical oxygen analysis. The variation mole ratios of citric acid and glycerol as well as temperature variations influences the value of the acid number and viscosity of the resulting lubricant. Temperatures is change from 90oC to 150oC can reduce the number of acids by 65% to 80%. The density of the lubricant is not affected significant by the variation of the operating conditions. The lubricant density value is in the range 1.29 - 1.36 g / ml. Increased polymerization temperatures and increased mole ratio of citric acid will increase the viscosity of the resulting lubricant. The oleic acid added to the lubricating polymerization process increases the viscosity value and decreases the density value. All the ratios of citric acid and glycerol have the same theoretical oxygen content of 54%. The kinetics of polymerization reactions as a function of the concentration of citric acid (CB) and temperature are 𝑟𝐵=13.893,82 𝑒−37.249,21 𝑅 𝑇(𝐾) 𝐶𝐵.